Comprehensive Assessment of Genetic and Molecular Features Predicting Outcome in Patients With Chronic Lymphocytic Leukemia: Results From the US Intergroup Phase III Trial E2997 - Grever, Michael R.; Lucas, David M.; Dewald, Gordon W.; Neuberg, Donna S.; Reed, John C.; Kitada, Shinichi; Flinn, Ian W.; Tallman, Martin S.; Appelbaum, Frederick R.; Larson, Richard A.; Paietta, Elisabeth; Jelinek, Diane F.; et al. (Journal of clinical oncology, 2007)
Genomic features including unmutated immunoglobulin variable region heavy chain (IgVH) genes, del(11q22.3), del(17p13.1), and p53 mutations have been reported to predict the clinical course and overall survival of patients with chronic lymphocytic leukemia (CLL). In addition, ZAP-70 and Bcl-2 family proteins have been explored as predictors of outcome. We prospectively evaluated the prognostic significance of a comprehensive panel of laboratory factors on both response and progression-free survival (PFS) using samples and data from 235 patients enrolled onto a therapeutic trial. Patients received either fludarabine (FL; n = 113) or fludarabine plus cyclophosphamide (FC; n = 122) as part of a US Intergroup randomized trial for previously untreated CLL patients. Complete response (CR) rates were 24.6% for patients receiving FC and 5.3% for patients receiving FL (P = .00004). PFS was statistically significantly longer in patients receiving FC (median, 33.5 months for patients receiving FC and 19.9 months for patients receiving FL; P < .0001). The occurrence of del(17p13.1) (hazard ratio, 3.428; P = .0002) or del(11q22.3) (hazard ratio, 1.904; P = .006) was associated with reduced PFS. CR and overall response rates were not significantly different based on cytogenetics, IgVH mutational status, CD38 expression, or p53 mutational status. Expression of ZAP-70, Bcl-2, Bax, Mcl-1, XIAP, Caspase-3, and Traf-1 was not associated with either clinical response or PFS. These results support the use of interphase cytogenetic analysis, but not IgVH, CD38 expression, or ZAP-70 status, to predict outcome of FL-based chemotherapy. Patients with high-risk cytogenetic features should be considered for alternative therapies.